1996
DOI: 10.1210/jc.81.7.2468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and age on the levels and circadian rhythmicity of plasma cortisol

Abstract: Data from rodent studies indicate that cumulative stress exposure may accelerate senescence and offer a theory to explain differences in the rate of aging. Cumulative exposure to glucocorticoids causes hippocampal defects, resulting in an impairment of the ability to terminate glucocorticoid secretion at the end of stress and, therefore, in increased exposure to glucocorticoids which, in turn, further decreases the ability of the hypothalamo-pituitary-adrenal axis to recover from a challenge. However, the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
409
9
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(461 citation statements)
references
References 0 publications
27
409
9
16
Order By: Relevance
“…In the present study, we used a manipulation that produces glucocorticoid levels that are clamped at the midpoint of the diurnal rhythm and hence are increased at the nadir but decreased at the zenith relative to the normal rhythm. The corticosterone profile generated is very similar to that seen in aged rats (Hauger et al, 1994) and similar to the profile of cortisol levels in aged human subjects (Deuschle et al, 1997a;Ferrari et al, 2001;Van Cauter et al, 1996;Wong et al, 2000). The elevated nadir and flattened rhythm is also consistent with the pattern observed in depressed patients, although in this group the peak of the diurnal rhythm is preserved, or even marginally elevated, resulting in an increase in 24 h cortisol exposure (Deuschle et al, 1997b;Wong et al, 2000).…”
Section: Relevance To Aging and Depressionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, we used a manipulation that produces glucocorticoid levels that are clamped at the midpoint of the diurnal rhythm and hence are increased at the nadir but decreased at the zenith relative to the normal rhythm. The corticosterone profile generated is very similar to that seen in aged rats (Hauger et al, 1994) and similar to the profile of cortisol levels in aged human subjects (Deuschle et al, 1997a;Ferrari et al, 2001;Van Cauter et al, 1996;Wong et al, 2000). The elevated nadir and flattened rhythm is also consistent with the pattern observed in depressed patients, although in this group the peak of the diurnal rhythm is preserved, or even marginally elevated, resulting in an increase in 24 h cortisol exposure (Deuschle et al, 1997b;Wong et al, 2000).…”
Section: Relevance To Aging and Depressionsupporting
confidence: 75%
“…However, more subtle changes in glucocorticoid levels are comparatively prevalent, and furthermore often go untreated. Thus in the normal aging process, there is a significant flattening of the normal diurnal rhythm of cortisol secretion (Ferrari et al, 2001;Van Cauter et al, 1996;Deuschle et al, 1997a). In addition, several common psychiatric disorders including affective disorders, cortisol secretion is moderately increased and there is a marked flattening of the diurnal rhythm (Deuschle et al, 1997b;Ferrari et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found an inverse relation between delta sleep and pulsatile cortisol release (see Vgontzas et al, 1999;Born et al, 1991 for a review). Normal aging is associated with a concurrent rise in secretory HPA activity and a reduction in delta sleep (Dodt et al, 1994;Feinberg et al, 1967;Gillin et al, 1981;Van Cauter et al, 1996). Aging is also associated with increased cortisol response and more decreases in delta sleep in response to mild laboratory stressors (Prinz et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found an age-associated increase in HPA activity (Van Cauter et al, 1996), resulting in elevated cortisol levels (Lupien et al, 1994;Ferrari et al, 1995;Deuschle et al, 1997) and attenuation, or a flattening, of cortisol diurnal rhythm (van Coevorden et al, 1991) suggesting age-dependent HPA axis dysregulation. Additionally, it has long been speculated that chronic elevations of stress-related hormones such as cortisol can weaken multiple physiological systems of older adults resulting in impaired cardiovascular and immune function, as well as contributing to dementia, and mood and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%